Repetitive Process Based Higher-order Iterative Learning Control Law Design - Maniarski, Robert; Paszke, Wojciech (1975- ); Chu, Bing; Rogers, Eric
This paper uses the repetitive process setting to develop new results on the design ofhigher-order ILC control laws. The basic idea of higher-order ILC is to use information froma finite number of previous trials, as opposed to just the last trial, to update the controlinput to be applied on the next trial, with the primary objective of improving the errorconvergence performance.
Keywords: Higher order ILC; linear matrix inequality; repetitive processes